EFEITO DA FRAÇÃO CRISTALINA E TAMANHO DE CRISTAL NA RESISTÊNCIA MECÂNICA E TENACIDADE À FRATURA DA VITROCERÂMICA DISSILICATO DE LÍTIO - Senk, Mariza Veiga (2017)
Glass-ceramic are obtained from the controlled crystallization of glasses and may exhibit different characteristics of the precursor glass. In this work we investigate the variation of the flexural strength and fracture toughness those were obtained by lithium disilicate glass-ceramic materials as a function of the size of the precipitate and the crystalline volumetric fractions, obtained by mechanical tests balls on three balls and flexion of four points, respectively. The temperatures used in the heat treatments were 460 ° C for nucleation and 538 ° C for crystalline growth. The mechanical properties of the glass ceramics varied in relation to the crystalline fraction. The flexural strength of the glassy sample was 117 11 MPa and for the samples with crystalline fraction of 98 % and precipitate with a diameter of 7 m was 297 22 MPa. The fracture toughness in lithium disilicate increases with the crystallized volumetric fraction, and the larger the grain size, the greater the value of KIC. The fracture toughness for the glass sample showed a value of 0,80 0,09 MPa:m0;5 and for the crystal of 34 and fraction of 80 %, KIC= 3,05 0,2 MPa:m0;5, an increase of 280 % on the glass.